Therapeutic potential of small extracellular vesicles derived from mesenchymal stem cells for spinal cord and nerve injury - Lim, Young-Ju; Jung, Gyeong Na; Park, Wook-Tae; Seo, Min-Soo; Lee, Gun Woo (Frontiers in Cell and Developmental Biology, 2023)
Neural diseases such as compressive, congenital, and traumatic injuries have diverse consequences, from benign mild sequelae to severe life-threatening conditions with associated losses of motor, sensory, and autonomic functions. Several approaches have been adopted to control neuroinflammatory cascades. Traditionally, mesenchymal stem cells (MSCs) have been regarded as therapeutic agents, as they possess growth factors and cytokines with potential anti-inflammatory and regenerative effects. However, several animal model studies have reported conflicting outcomes, and therefore, the role of MSCs as a regenerative source for the treatment of neural pathologies remains debatable. In addition, issues such as heterogeneity and ethical issues limited their use as therapeutic agents. To overcome the obstacles associated with the use of traditional agents, we explored the therapeutic potentials of extracellular vesicles (EVs), which contain nucleic acids, functional proteins, and bioactive lipids, and play crucial roles in immune response regulation, inflammation reduction, and cell-to-cell communication. EVs may surpass MSCs in size issue, immunogenicity, and response to the host environment. However, a comprehensive review is required on the therapeutic potential of EVs for the treatment of neural pathologies. In this review, we discuss the action mechanism of EVs, their potential for treating neural pathologies, and future perspectives regarding their clinical applications.